Emigration from Europe, 1815-1930 - Baines, Dudley; Economic History Society (Cambridge ; New York : Cambridge University Press, 1995)
Based on research findings from more than 12 European countries, this book is concerned with the reason why about 60 million people left Europe for overseas destinations. The key issue is taken to be the incidence of emigration
Includes bibliographical references and index.
Keywords: Europe. -- Emigration and immigration -- History; Europe -- Emigration and immigration -- History